'I Want Everyone to Have It, and Everyone to Be on It': A Feasibility Study of the Transforming Long Covid Intervention. - Belton, Sarahjane; Goss, Hannah; Whyte, Enda; McCaffrey, Noel; Gibney, Sophie; Sheridan, Kate (Health Expectations, 2026)
Background: An understanding of the nature of long Covid (LC) is evolving, with recent evidence highlighting the role of increased sympathetic activation and decreased parasympathetic response. Building upon this emerging science, the 'Transforming Long COVID' (TLC) programme was developed to support participants in their recovery by (i) introducing education on the neuroscience underpinning persistent symptoms (with a particular focus on the autonomic nervous system) and (ii) the development of self‐management strategies to support recovery. The aim of this study was to examine the feasibility of the TLC programme with a cohort of people significantly affected by LC. Methods: Seventeen participants took part in the 8‐week TLC programme which comprised of seven content sessions and one discussion (Q&A) session. Participants completed survey scales (investigating anxiety, pain‐related interference, pain catastrophising, sleep disturbance and fatigue) at baseline, immediately post‐programme (at 8 weeks), and retention (at 13 weeks). Participants also took part in focus group interviews to investigate their experiences of the programme. Results: Fourteen participants (82%) attended at least six of the seven TLC content sessions. Decreases in mean values over time were observed across all measures, indicating a positive (non‐significant) change. Participants reported an increase in understanding of LC, new hope for recovery, belief that they now had a realistic pathway for recovery, validation of their experiences and symptoms, meaningful improvements in function, and enhanced ability to respond to and attenuate physical symptoms. No adverse events were reported. Participants highlighted a number of programme strengths, along with some potential areas for improvement. Conclusion: The TLC programme was shown to be feasible based on engagement, adherence, acceptable completion of surveys, and no adverse events. Study findings point to the potential for this programme to be refined, trialled and evaluated with a larger sample. Patient or Public Contribution: Four people (living with LC, ME/CFS, chronic migraine and chronic Lyme, fibromyalgia, and centralised pain syndrome), who have experience of applying a recovery approach aligned with the TLC programme, acted in a PPI (Public and Patient Involvement in research) capacity on this study. In addition, the lead author has personal experience with the illness, and developing the recovery approach, which helped inform programme structure and development [1]. These individuals provided advice and guidance on the potential structure for the group programme, course duration, tool selection, and language and wording of the programme and materials. Further detail is provided in the Supplementary Materials.